The impact of a 12-week high-intensity interval training program on popliteal vascular responses to prolonged sitting - Haoxuan Liu; Sophie E. Rayner; Beverly D. Schwartz; Yanlin Wu; Jennifer L. Petterson; Myles W. O’Brien; Derek Stephen Kimmerly (European Journal of Applied Physiology, 2026)

Metabolic cost of external work: a novel CPET parameter optimises characterisation of exercise performance in obese individuals - Jennifer J. Rayner; Rebecca R. Chamley; Robert Barker Davies; Oliver O’Sullivan; Peter Ladlow; Alex N. Bennett; Edward D. Nicol; Oliver J. Rider; David A. Holdsworth (European Journal of Applied Physiology, 2026)
Purpose Both obesity and cardiorespiratory fitness are crucial determinants of symptoms and prognosis. However, interpreting the gold-standard cardiopulmonary exercise test (CPET) is complicated by increasing body size and varying body composition. We hypothesised that the ‘metabolic cost of external work’ (or oxygen uptake (ml/min)/workload (Watts); V̇O 2 /W), a body weight-independent determinant of endurance capacity, would reflect metabolic health more accurately than V̇O 2 alone. Methods A test cohort of 160 fit individuals underwent anthropomorphic and metabolic assessment, maximal bicycle ergometer CPET, and six-minute walk test (6MWT). V̇O 2 /W was calculated at VT1 and peak. The performance of V̇O 2 /W was validated in 62 older, less fit individuals, undergoing the same protocol. 24 obese volunteers were assigned a weight loss intervention, and the impact on V̇O 2 /W examined. Results In both test and validation cohort, V̇O 2 /W at VT1 and peak correlated with 6MWT distance, more strongly than standard CPET parameters. Including V̇O 2 /W improved the accuracy of predicting 6MWT distance. V̇O 2 /W correlated with BMI, insulin sensitivity and waist-to-hip ratio. Metabolic cost falls with weight loss, in parallel to metabolic and functional improvements, in contrast to other CPET parameters. Conclusion Metabolic cost is strongly associated with functional capacity and metabolic health across a range of body weight and fitness, outperforming standard CPET metrics. It is a simple measure which may improve our assessment of the extent to which exertional symptoms are determined by metabolic factors in an individual, and thereby target the most appropriate intervention to those who will benefit most. Graphical Abstract

Corrigendum to “Synthesis of controlled size starch nanoparticles (SNPs) title of article” [Carbohydr. Polym. 250 (2020) 116938] - G. Gutiérrez; D. Morán; A. Marefati; J. Purhagen; M. Rayner; M. Matos (Carbohydrate Polymers, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Exploring uncertainty reduction in high-resolution methane emissions in Gippsland through in-situ data: A Bayesian inverse modeling and variational assimilation method - Sougol Aghdasi; Peter J. Rayner; Nicholas M. Deutscher; Jeremy D. Silver (Atmospheric Research, 2025)

The combination of neurotropic B vitamins (B1, B6, and B12) is superior to individual B vitamins in promoting neurite growth in vitro - Melissa L. D. Rayner; Arnaud J. Ruiz; Christian Viel (In Vitro Cellular & Developmental Biology - Animal, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Natural Source Zone Depletion of crude oil, gasoline, diesel and aviation gasoline petroleum in the same soil/aquifer system – An intensive intercomparison field study and simulation - John L. Rayner; Mike J. Donn; Greg B. Davis; Trevor P. Bastow; Kaveh Sookhak Lari; Colin D. Johnston; Andrew King; Andrew Furness (Science of The Total Environment, 2024)

Upscaling the remediation of acidic landscapes – the coastal floodplain prioritisation method - K. Waddington; A. Harrison; D. Rayner; T. Tucker; W. Glamore (Journal of Environmental Management, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Toxic effects of lead in plants grown in brazilian soils - Geraldo S. Cândido; Gabriel C. Martins; Isabela C. F. Vasques; Francielle R. D. Lima; Polyana Pereira; Mateus M. Engelhardt; Rayner H. C. L. Reis; João José Marques (Ecotoxicology, 2020)

Evaluation of mercury phytoavailability in Oxisols - Francielle R. D. Lima; Mateus M. Engelhardt; Isabela C. F. Vasques; Gabriel C. Martins; Geraldo S. Cândido; Polyana Pereira; Rayner H. C. L. Reis; Aline O. Silva; Luiz Roberto G. Guilherme; João José Marques (Environmental Science and Pollution Research, 2019)

Dominant regions and drivers of the variability of the global land carbon sink across timescales - Xuanze Zhang; Ying‐Ping Wang; Shushi Peng; Peter J. Rayner; Philippe Ciais; Jeremy D. Silver; Shilong Piao; Zaichun Zhu; Xingjie Lu; Xiaogu Zheng (Global Change Biology, 2018)
Net biome productivity ( NBP ) dominates the observed large variation of atmospheric CO 2 annual increase over the last five decades. However, the dominant regions controlling inter‐annual to multi‐decadal variability of global NBP are still controversial (semi‐arid regions vs. temperate or tropical forests). By developing a theory for partitioning the variance of NBP into the contributions of net primary production ( NPP ) and heterotrophic respiration ( R h ) at different timescales, and using both observation‐based atmospheric CO 2 inversion product and the outputs of 10 process‐based terrestrial ecosystem models forced by 110‐year observational climate, we tried to reconcile the controversy by showing that semi‐arid lands dominate the variability of global NBP at inter‐annual ( 30 years). Results further indicate that global NBP variability is dominated by the NPP component at inter‐annual timescales, and is progressively controlled by R h with increasing timescale. Multi‐decadal NBP variations of tropical rainforests are modulated by the Pacific Decadal Oscillation ( PDO ) through its significant influences on both temperature and precipitation. This study calls for long‐term observations for the decadal or longer fluctuations in carbon fluxes to gain insights on the future evolution of global NBP , particularly in the tropical forests that dominate the decadal variability of land carbon uptake and are more effective for climate mitigation.

ICOADS Release 3.0: a major update to the historical marine climate record - Eric Freeman; Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Elizabeth C. Kent; William E. Angel; David I. Berry; Philip Brohan; Ryan Eastman; Lydia Gates; Wolfgang Gloeden; Zaihua Ji; et al. (International Journal of Climatology, 2017)
We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set ( ICOADS ) in the latest Release 3.0 ( R3 .0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3 .0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS , reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS ' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced ‘preliminary’ monthly data and product extensions past 2014, R3 .0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Multi-species chemical data assimilation with the Danish Eulerian hemispheric model: system description and verification - Jeremy D. Silver; Jesper H. Christensen; Michael Kahnert; Lennart Robertson; Peter J. Rayner; Jørgen Brandt (Journal of Atmospheric Chemistry, 2016)

Compensation between meridional flow components of the Atlantic MOC at 26° N - E. Frajka-Williams; C. S. Meinen; W. E. Johns; D. A. Smeed; A. Duchez; A. J. Lawrence; D. A. Cuthbertson; G. D. McCarthy; H. L. Bryden; M. O. Baringer; B. I. Moat; D. Rayner (Ocean Science, 2016)
From ten years of observations of the Atlantic meridional overturning circulation (MOC) at 26° N (2004–2014), we revisit the question of flow compensation between components of the circulation. Contrasting with early results from the observations, transport variations of the Florida Current (FC) and upper mid-ocean (UMO) transports (top 1000 m east of the Bahamas) are now found to compensate on sub-annual timescales. The observed compensation between the FC and UMO transports is associated with horizontal circulation and means that this part of the correlated variability does not project onto the MOC. A deep baroclinic response to wind-forcing (Ekman transport) is also found in the lower North Atlantic Deep Water (LNADW; 3000–5000 m) transport. In contrast, co-variability between Ekman and the LNADW transports does contribute to overturning. On longer timescales, the southward UMO transport has continued to strengthen, resulting in a continued decline of the MOC. Most of this interannual variability of the MOC can be traced to changes in isopycnal displacements on the western boundary, within the top 1000 m and below 2000 m. Substantial trends are observed in isopycnal displacements in the deep ocean, underscoring the importance of deep boundary measurements to capture the variability of the Atlantic MOC.

Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Model–data synthesis in terrestrial carbon observation: methods, data requirements and data uncertainty specifications - M. R. Raupach; P. J. Rayner; D. J. Barrett; R. S. DeFries; M. Heimann; D. S. Ojima; S. Quegan; C. C. Schmullius (Global Change Biology, 2005)
Systematic, operational, long‐term observations of the terrestrial carbon cycle (including its interactions with water, energy and nutrient cycles and ecosystem dynamics) are important for the prediction and management of climate, water resources, food resources, biodiversity and desertification. To contribute to these goals, a terrestrial carbon observing system requires the synthesis of several kinds of observation into terrestrial biosphere models encompassing the coupled cycles of carbon, water, energy and nutrients. Relevant observations include atmospheric composition (concentrations of CO 2 and other gases); remote sensing; flux and process measurements from intensive study sites; in situ vegetation and soil monitoring; weather, climate and hydrological data; and contemporary and historical data on land use, land use change and disturbance (grazing, harvest, clearing, fire). A review of model–data synthesis tools for terrestrial carbon observation identifies ‘nonsequential’ and ‘sequential’ approaches as major categories, differing according to whether data are treated all at once or sequentially. The structure underlying both approaches is reviewed, highlighting several basic commonalities in formalism and data requirements. An essential commonality is that for all model–data synthesis problems, both nonsequential and sequential, data uncertainties are as important as data values themselves and have a comparable role in determining the outcome. Given the importance of data uncertainties, there is an urgent need for soundly based uncertainty characterizations for the main kinds of data used in terrestrial carbon observation. The first requirement is a specification of the main properties of the error covariance matrix. As a step towards this goal, semi‐quantitative estimates are made of the main properties of the error covariance matrix for four kinds of data essential for terrestrial carbon observation: remote sensing of land surface properties, atmospheric composition measurements, direct flux measurements, and measurements of carbon stores.

Grain-scale variations in trace element composition of fluid-altered zircon, Acasta Gneiss Complex, northwestern Canada - N. Rayner; R. A. Stern; S. D. Carr (Contributions to Mineralogy and Petrology, 2005)

Regulation of leptin production: sympathetic nervous system interactions - D. Vernon Rayner; Paul Trayhurn (Journal of Molecular Medicine, 2001)

The Kwinana Coastal Fumigation Study: I – Program Overview, Experimental Design and Selected Results - B. L. Sawford; A. K. Luhar; J. M. Hacker; S. A. Young; I. -H. Yoon; J. A. Noonan; J. N. Carras; D. J. Williams; K. N. Rayner (Boundary-Layer Meteorology, 1998)